2015
DOI: 10.1111/tmi.12610
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in adult immigrants in the 2000s in Belgium: a test of the ‘healthy‐migrant’ and the ‘migration‐as‐rapid‐health‐transition’ hypotheses

Abstract: Abstractobjective Firstly, to map out and compare all-cause and cause-specific mortality patterns by migrant background in Belgium; and secondly, to probe into explanations for the observed patterns, more specifically into the healthy-migrant, acculturation and the migration-as-rapid-health-transition theories.methods Data comprise individually linked Belgian census-mortality follow-up data for the period 2001-2011. All official inhabitants aged 25-54 at time of the census were included. To delve into the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
120
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(135 citation statements)
references
References 36 publications
10
120
2
Order By: Relevance
“…Mortality from cancer of the digestive tract was lower for Sub-Saharan Africans, Italians, Spaniards, and Moroccans. A recent study taking into account duration of residence and immigrant generation shows increased all-cancer and lung cancer mortality with longer residence in Belgium and in the second generation (SG) [12]. Additionally, socio-economic position (SEP) and urbanisation contribute to site-specific cancer mortality levels for all groups [12].…”
Section: Introductionmentioning
confidence: 99%
“…Mortality from cancer of the digestive tract was lower for Sub-Saharan Africans, Italians, Spaniards, and Moroccans. A recent study taking into account duration of residence and immigrant generation shows increased all-cancer and lung cancer mortality with longer residence in Belgium and in the second generation (SG) [12]. Additionally, socio-economic position (SEP) and urbanisation contribute to site-specific cancer mortality levels for all groups [12].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there is an argument for strongly targeting health promotion campaigns at first generation individuals to discourage uptake of high-risk health behaviours and encourage cessation of unhealthy behaviours such as unhealthy eating and smoking (Vandenheede et al, 2015). 22 Our findings indicated that cancer-related information provided by large government and charitable organisations was not specifically focused on black men; current information formats were unappealing even when they featured black men.…”
Section: Implications For Practice and Researchmentioning
confidence: 83%
“…For example, our study indicated differences between the views of first and second generation participants. Other studies have reported a 'healthy migrant' advantage for first generation immigrants to a host country, regardless of socioeconomic position (Anson, 2004;Tarnutze et al, 2012;Vandenheede et al, 2015).…”
Section: Implications For Practice and Researchmentioning
confidence: 97%
See 1 more Smart Citation
“…Shortly, the hypothesis of migration as 'accelerated health transition' predicts a fast decline of the initially high infectious-disease mortality of migrants and a progressive reduction of their advantage in terms of chronic disease mortality over time. Very few studies have investigated this hypothesis to date (Vandenheede et al, 2015;Wallace and Kulu, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%